Seismic Vulnerability Analysis of Multispan Continuous Bridges Subjected to Mainshock-Aftershock Earthquake Sequences - Yan Liang; Yukun Cui; Chao Ren (Advances in Civil Engineering)
A multispan continuous 3D bridge model is established on the basis of OpenSees platform, and 160 mainshock-aftershock (MA) sequences are constructed in accordance with the bridge site to study their influence on the seismic vulnerability of bridges. The seismic vulnerability of bridge piers, bearings, and abutments subjected to MA sequences is investigated. The influence of MA sequences on the seismic vulnerability of the bridge system is also analysed using first- and second-order boundary estimation methods. Results show that the seismic response and exceedance probability of the bridge components and system subjected to MA sequences are significantly increased compared with those under the consideration of mainshock only. The second-order boundary estimation method based on component correlation coefficient can significantly reduce the upper and lower limit widths of the vulnerability curves and improve the accuracy. Under the same peak ground acceleration (PGA) and damage state, the exceedance probability of the bridge system is higher than that of any component in the system. The exceedance probability under different damage states of the bridge components and system increases with the PGA. For any given PGA, the exceedance probability decreases with the increase in severity of damage state.